Determinants of gender-equitable attitudes among adult men in a health education program: a cross-sectional study in Southern Malawi - Isotta Triulzi; Stefano Orlando; Ilaria Palla; Bryan Mthiko; Alinane Linda Nyondo-Mipando; Sangaré Hawa Mamary; Tambwali Bruce Playster; Fausto Ciccacci; Cristina Maria Marazzi; Giuseppe Turchetti (BMC Public Health)
Abstract Background Malawi ranks 142 out of 170 countries on the UN’s Gender Inequality Index (GII). Women and men in Malawi have unequal access to and control over resources. Previous research has primarily examined gender roles and norms from a women’s perspective, but few studies have investigated men’s attitudes and behaviors regarding gender equality. This study fills this gap by investigating the social factors that influence attitudes towards gender-equality and exploring the association between behaviors and attitudes in south-eastern Malawi. Methods A cross-sectional survey was administered to adult males during a health education program (male-friendly clinics) in four healthcare facilities from August 2022 to November 2022. The validated Gender-Equitable Men (GEM) scale, was employed to quantify men’s attitudes towards gender norms. Univariate and multivariable analyses were used to identify the social determinants of and the behaviors associated with gender-equitable attitudes. Results A total of 422 men, with a median age of 46 years (IQR = 34, 55), were included in this study. The participants reported a median score of 0.53 for gender attitudes, where 0 represents the minimum score and 1 the maximum. A higher GEM score was associated with a higher educational grade and living in an urban area. In terms of decision-making, 64% and 56% of men reported that they had the final say in matters concerning women’s and children’s health, respectively. Higher GEM scores were associated with joint decision-making in relation to women’s (0.55 vs. 0.49; p = 0.008) and children’s health (0.54 vs. 0.48; p = 0.012), and spending on food and clothing (0.56 vs. 0.49; p < 0.001). On the other hand, certain activities, such as cleaning the house (64% of men reported unequal participation), and cooking (70%) were not shared among partners. An equal or greater participation from men (70%) compared to women was reported for activities related to childcare. Men who participated in the previously mentioned tasks had higher GEM scores than those who did not. Conclusions The findings of this study shed light on the significant role of educational grade and living in an urban area as determinants of gender-equitable attitudes among men in south-eastern Malawi. More equitable perspectives towards gender norms were associated with being more involved in tasks typically assigned to women and in joint decision-making. Incorporating gender in research can contribute to the advancement of a more inclusive healthcare system.